Lokakarya Berbasis Eksperimen sebagai Upaya Peningkatan Literasi Sains Siswa Sekolah Dasar: Pengenalan Konsep Indikator pH Alami Melalui Tinta Tak Terlihat - Tan, Watumesa Agustina; Christanto, James Elliot; Wibowo, Ronald Kristianto; Karmawan, Listya Utami (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance elementary school students’ understanding of and interest in science through the implementation of interactive experiments based on the concept of natural pH indicators. The program was conducted at SD Athalia, Tangerang, involving 132 fifth-grade students who were divided into five groups of 26–27 students to ensure active participation. The implementation stages included an introduction to basic pH concepts, experimental demonstrations, and hands-on activities in which students created drawings using “invisible ink” made from a baking soda solution as a basic substance and turmeric as a natural pH indicator. The turmeric solution changed color from yellow to reddish-brown in areas that reacted with the base, revealing previously hidden images. The results indicate high levels of student enthusiasm, active participation, and curiosity toward science learning. These findings demonstrate that simple, activity-based experimental approaches are effective in fostering students’ interest in and initial understanding of science, while also representing a tangible contribution of higher education institutions to improving community science literacy.